Market-based instruments for ecosystem services: framework and case study in Lishui City, China - Xiaolong Gao; Weihua Xu; Ying Hou; Zhiyun Ouyang (Ecosystem Health and Sustainability, 2020)
Introduction: Effective provision of ecosystem services (ES) and improvements in well-being of residents can be realized through policy interventions of stakeholder behavior. Of the several policies, market-based instruments (MBIs) have become the focus of global attention. Outcomes/others: To couple the theory with practice and solve the key problem of unclear definition of property rights, the framework of MBIs is designed. First, property rights of market creation must be clearly defined, verifiable, transferable, enforceable, and have policy continuity. Then, four key characteristics of MBIs need to be considered in the case design, namely those involving ES, stakeholders, trading mechanisms, and guarantee mechanisms. The Pledge Financing of the Right of the Ecological Public Welfare Forest (PFREPWF) in Lishui City is a typical case of China’s current marketization, which is a supplement and improvement to the ecological compensation policy. Based on clearly defined contract rights, Lishui City has realized the integration of ecological compensation and credit creation. Discussion: The case design still has the problems of lack of quantification and lack of correlations with ES. Conclusion: The theoretical and practical analysis around the market mechanism has reference value for solving market failures and providing environmental services.